NATUR DAN PERAN RASIO DALAM APOLOGETIKA KRISTEN - Yonathan Wijaya Lo (STT Amanat Agung, 2014)
God has provided the soul of man with intellect, by which he might discern good from evil, just from unjust, and might know what to follow of to shun, reason going begore with her lamp. To this he has joined will, to which choice belongs. Man excelled in these endowments in his primitive condition, when reason, intelligence, prudence, and justment not sufficed for the government of his earthly life, but also enabled him to rise up to God, and eternal happiness. (John Calvin, Institutes, I. 1. 15.8)